Protective Effect of Rumex vesicarius L. Leaf Extract against Paracetamol-Induced Hepatorenal Oxidative Injury in Wistar Rats - Mashaalaah Hamed, Yathrib (Libyan Journal of Medical and Applied Sciences, 2026)
Paracetamol overdose-induced hepatic injury continues to be an important problem and may also be associated with clinically significant renal damage through mechanisms that involve formation of reactive metabolites, glutathione depletion, oxidative stress, mitochondrial dysfunction, and secondary inflammatory amplification. This study aimed to evaluate the protective effect of leaf extract of Rumex vesicarius L. against paracetamol-induced oxidative damage to liver and kidneys in normal Wistar rats. This is achieved by integrating pharmacognostic standardization, physiological relevance, and mechanistic pharmacology. A hydroalcoholic leaf extract was evaluated in a rat model of paracetamol toxicity using serum biochemical markers of liver and kidney function, tissue oxidative stress indices, antioxidant enzyme activities, inflammatory cytokines, and histopathological evaluation of both organs. The result showed that paracetamol causes big rises of serum transaminases, alkaline phosphatase, bilirubin, urea, blood urea nitrogen, creatinine, tissue malondialdehyde, and pro-inflammatory cytokines. It also decreased the levels of glutathione and enzymatic antioxidant defenses. The Rumex vesicarius extract decreased these changes in a dose-dependent manner and preserved the hepatic and renal architecture histologically. Collectively, the results support the notion that a leaf extract of R. vesicarius protective profile is due to its ability to cooperate with other antioxidants, anti-inflammatories and tissue-preserving agents.